Cervical Cancer-Associated Suffering: Estimating the Palliative Care Needs of a Highly Vulnerable Population. (2021) - Krakauer, Eric L.; Kwete, Xiaoxiao; Kane, Khadidjatou; Afshan, Gauhar; Bazzett-Matabele, Lisa; Bien-Aimé, Danta Dona Ruthnie; Byrne-Martelli, Sarah; Connor, Stephen; Correa, Raimundo; Devi, C. R. Beena; Diop, Mamadou; Gafer, Nahla; et al.
Abstract : PURPOSE: To enable design of optimum palliative care for women with cervical cancer, we studied the most common types of suffering and their severity, prevalence, and duration. METHODS: We first reviewed the literature on the major types, severity, prevalence, and duration of suffering associated with cervical cancer. We then conducted a modified Delphi process with experts in cervical cancer care to supplement the literature. For each type of suffering, we distinguished between decedents (those who die from cervical cancer in a given year) and nondecedents (those who have cervical cancer in a given year but do not die). By applying the suffering prevalence and duration estimates to the number of decedents, nondecedents, and family caregivers in 2017, we were able to estimate their palliative care needs and the intensity of palliative care needed to respond adequately to this suffering. RESULTS: There is a high prevalence among decedents of moderate or severe pain (84%), vaginal discharge (66%), vaginal bleeding (61%), and loss of faith (31%). Among both decedents and nondecedents, there is a high prevalence of clinically significant anxiety (63% and 50%, respectively), depressed mood (52% and 38%, respectively), and sexual dysfunction (87% and 83%, respectively). Moderate or severe financial distress is prevalent among decedents, nondecedents, and family caregivers (84%, 74%, and 66%, respectively). More than 40% of decedents and nondecedents are abandoned by their intimate partners. Most patients experience some combination of moderate or severe physical, psychological, social, and spiritual suffering. In total, 258, 649 decedents and 2, 558, 857 nondecedents needed palliative care in 2017, approximately 85% of whom were in low- and middle-income countries where palliative care is rarely accessible. CONCLUSION: Among women with advanced cervical cancer, suffering is highly prevalent and often severe and multifaceted.